Neighbourhood‐mediated shifts in tree biomass allocation drive overyielding in tropical species mixtures. Issue 4 (9th July 2020) - Guillemot, Joannès; Kunz, Matthias; Schnabel, Florian; Fichtner, Andreas; Madsen, Christopher P.; Gebauer, Tobias; Härdtle, Werner; von Oheimb, Goddert; Potvin, Catherine
Summary: Variations in crown forms promote canopy space‐use and productivity in mixed‐species forests. However, we have a limited understanding on how this response is mediated by changes in within‐tree biomass allocation. Here, we explored the role of changes in tree allometry, biomass allocation and architecture in shaping diversity–productivity relationships (DPRs) in the oldest tropical tree diversity experiment. We conducted whole‐tree destructive biomass measurements and terrestrial laser scanning. Spatially explicit models were built at the tree level to investigate the effects of tree size and local neighbourhood conditions. Results were then upscaled to the stand level, and mixture effects were explored using a bootstrapping procedure. Biomass allocation and architecture substantially changed in mixtures, which resulted from both tree‐size effects and neighbourhood‐mediated plasticity. Shifts in biomass allocation among branch orders explained substantial shares of the observed overyielding. By contrast, root‐to‐shoot ratios, as well as the allometric relationships between tree basal area and aboveground biomass, were little affected by the local neighbourhood. Our results suggest that generic allometric equations can be used to estimate forest aboveground biomass overyielding from diameter inventory data. Overall, we demonstrate that shifts in tree biomass allocation are mediated by the local neighbourhood and promote DPRs in tropical forests. Abstract : See also the Commentary on this article by Cushman & Machado 228 : 1163–1165 .